ON M- Hollow modules - Baghdad Science Journal (مجلة بغداد للعلوم, 2010)
Let R be associative ring with identity and M is a non- zero unitary left module over R. M is called M- hollow if every maximal submodule of M is small submodule of M. In this paper we study the properties of this kind of modules.